How does open innovation promote circular economy practices? Evidence from Chinese listed companies - Xingmin Yin; Yun Jin; Zhou Li; Yulin Liu (Journal of Innovation & Knowledge (JIK), 2025)
Although firms contend with multiple challenges in implementing circular economy (CE) practices, open innovation (OI) can be an effective collaborative strategy for firms to overcome technological and informational barriers and achieve CE objectives. Using data from A-share and Science and Technology Innovation Board (STAR Market) listed companies in China from 2003 to 2022, we employ a two-way fixed effects model to examine the impact of OI on firms' CE practices. The empirical results indicate that OI significantly promotes CE practices, influencing these practices through mechanisms such as trade credit provision, green patent accumulation, and enhanced information exchange. Moreover, government CE policies can strengthen the effect of OI on CE practices. Additionally, intercompany OI has a stronger positive impact on CE practices compared with intracompany and cooperative OI. The effects of OI and the moderating influence of CE policies are more pronounced in the eastern region, which is likely driven by superior industrialization in the region. These findings clarify the relationship between OI and CE practices to advance global CE practices. Future research could explore broader datasets, adopt alternative OI indicators, and conduct cross-country comparisons to further expand this research.
Keywords: C30; E60; E70; Q05; O36; 650; Open innovation; Circular economy practices; Trade credit; Green patents; Circular economy policies